Risk factors for visual impairment associated with corneal diseases in southern China - Xu SC (Dove Medical Press, 2016)
Sarah C Xu,1 Jessica Chow,1 Ji Liu,1 Liang Li,2 Jessica S Maslin,1 Nisha Chadha,1 Baihua Chen,2 Christopher C Teng1 1Department of Ophthalmology and Visual Science, Yale University School of Medicine, New Haven, CT, USA; 2Department of Ophthalmology, The Second Xiangya Hospital of Central South University, Changsha, People’s Republic of China Purpose: To identify the most common etiologies of corneal disease and the risk factors associated with worse visual outcomes in Changsha, Hunan, located in southern China. Methods: This observational, cross-sectional study evaluated 100 consecutive patients seen at the cornea clinic of The Second Xiangya Hospital of Central South University. Ocular history, demographic information, and ocular use of traditional Chinese medicine were recorded and analyzed. Causes of infectious keratitis were diagnosed clinically. Fungal and acanthamoeba keratitis were confirmed by confocal microscopy. Visual impairment was categorized based on visual acuity according to World Health Organization recommendations. A binary logistic regression model was used to calculate odds ratio (OR). Results: One hundred consecutive patients were evaluated. Sixty patients (60%) had noninfectious corneal diseases, most commonly dry eye syndrome (26.7%, n=16), followed by corneal abrasion (18.3%, n=11). Forty-five patients had infectious keratitis, five of whom had both infectious and noninfectious etiologies. Of the patients with infectious keratitis, viral keratitis was the most frequent cause (57.8%, n=26), followed by fungal (20%, n=9) and bacterial (20%, n=9). Older age (OR =5.08, P=0.048), male sex (OR =3.37, P=0.035), and rural residence (OR =3.11, P=0.017) had increased odds of having worse visual impairment. Rural residence was also associated with infectious keratitis (P=0.005), particularly bacterial and fungal keratitis (P=0.046), and a history of ocular trauma (P=0.003). Occupation was not a significant risk factor in this population. Fourteen patients reported use of traditional Chinese medicine, with no association with visual outcomes found. Conclusion: Older age, male sex, and rural residence were associated with worse visual impairment. Prevalence and outcome of corneal diseases may be improved with an increased awareness in these populations. Keywords: rural area, international ophthalmology, corneal diseases, traditional Chinese medicine